A philosophical analysis of anti‐intellectualism in nursing: Newman's view of a university education. (22nd June 2021) - Racine, Louise; Vandenberg, Helen
Abstract: Canadian and international nursing educators are increasingly concerned with the quality of university nursing education. Contemporary nursing education is fraught by a growing anti‐intellectualism coupled with the dominance of neoliberalism and corporate university business culture. Amid these challenges, nursing schools must prepare nurses to provide care in an era compounded by social and health inequities. The purpose of this paper was to explore the philosophical and contextual factors influencing anti‐intellectualism in nursing education. We use John Henry Newman's view of the purpose of a university education as a heuristic perspective to examine anti‐intellectualism in nursing. We contend that the ideological worship of technological advances, a culture of consumerism, quality improvement and risk management, the primacy of doing over thinking, competency‐based curricula and business models rooted in neoliberal financial policies reinforce anti‐intellectualism in nursing. Anti‐intellectualism is a complex issue to address within the corporate university culture. We propose multiple strategies at the disciplinary, university and sociopolitical levels to decrease anti‐intellectualism. Counteracting anti‐intellectualism requires critical thinking, praxis and emancipation. Nurses should critically examine this anti‐intellectual trend as it limits the advancement of the discipline and marginalizes its contributions within the academy. If nurses do not address this challenge, the survival of nursing as an academic discipline may be jeopardized.